Pengaruh Profitabilitas, Thin Capitalization, Sales Growth dan Kepemilikan Institusional terhadap Tax Avoidance - Bandang, Agus; Tristan Sarodjie, Kenzy Noel; Haerial, Haerial; Mahfiza, Mahfiza (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to examine the effect of profitability, thin capitalization, sales growth, and institutional ownership on tax avoidance, both partially and simultaneously, with the research subject being property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) from 2018-2022. This study uses a quantitative method with secondary data sources. Thedata analysis techniqueused is multiple linear regression using SPSS Version 26. The population subject consists of 61 companies, with a sample of 11 companies. The results of the study indicate that, partially, profitability has a positive but not significant effect on tax avoidance. Thin capitalization has a positive and significant effect on tax avoidance. Sales growth has a negative and significant effect on tax avoidance, and institutional ownership has a positive and significant effect on tax avoidance. Meanwhile, simultaneously, profitability, thin capitalization, sales growth, and institutional ownership have a positive and significant effect on tax avoidance.